Peran Pesantren Modern Terhadap Pembentukan Karakter Kepemimpinan Santri - Fatmawati Fatmawati; Gusti Katon; Ro'id Naufal Sulistiyono; Saivy Ilma Diany (Al-Fikr: Jurnal Pendidikan Islam, 2020)
The writing of this paper aims to study and add a little insight as well as some important opinions and pointsrelated to modern pesantren on the formation of the student leadership character, how to shape thesecharacters, how to carry out the responsible tasks that must be carried out, an understanding of thecharacter, etc. This study uses a literature review method (literature) of relevant sources related to the titleof the role of modern pesantren in shaping the character of student leadership. For the sake of formingleaders with character, modern boarding schools are not only me who manage, teach, and lead parts. Butrather educate the whole life as a whole and get involved with armed with faith, knowledge, charity,morality, communication/interaction, and mentally tough. Ask leaders who have to argue, always getapproval, don't want to wait, can make work, and don't look for work.